A Qualitative Understanding of Patient Falls in Inpatient Mental Health Units. (September 2014) - Powell-Cope, Gail; Quigley, Patricia; Besterman-Dahan, Karen; Smith, Maureen; Stewart, Jonathan; Melillo, Christine; Haun, Jolie; Friedman, Yvonne
BACKGROUND: Falls are the leading cause of injury-related deaths among people age 65 and older, and fractures are the major category of serious injuries produced by falls.OBJECTIVE: Determine market segment–specific recommendations for "selling" falls prevention in acute inpatient psychiatry.DESIGN: Descriptive using focus groups.SETTING: One inpatient unit at a Veterans' hospital in the Southeastern United States and one national conference of psychiatric and mental health nurses.PATIENTS: A convenience sample of 22 registered nurses and advanced practice nurses, one physical therapist and two physicians participated in one of six focus groups.INTERVENTION: None.MEASUREMENTS: Focus groups were conducted by expert facilitators using a semistructured interview guide. Focus groups were recorded and transcribed. Content analysis was used to organize findings.RESULTS: Findings were grouped into fall risk assessment, clinical fall risk precautions, programmatic fall prevention, and "selling" fall prevention in psychiatry. Participants focused on falls prevention instead of fall injury prevention, were committed to reducing risk, and were receptive to learning how to improve safety. Participants recognized unique features of their patients and care settings that defined risk, and were highly motivated to work with other disciplines to keep patients safe.CONCLUSIONS: Selling fall injury prevention to staff in psychiatric settings is similar to selling fall injury prevention to staff in other health care settings. Appealing to the larger construct of patient safety will motivate staff in psychiatric settings to implement best practices and customize these to account for unique population needs characteristics.